Religion, Science and Non-science - Raphael Neelamkavil (Journal of Dharma, 2004)
The inception of anything new (here, science since Galileo and Darwin) should prove to be disastrous (here, science’s seeming antagonism to religion). The initial and seemingly ongoing conflict is, in fact, between scientific dogmas and practices that threaten to be more adequate than those of religion and religious practices and definitions of beliefs that always trade antiques with respect to both the blatantly scientific mind and the deeply intellectually and practically religious soul. As this question is not scientific or religious, it can only be philosophical and epistemological, in particular. Dharmaram Publications is now ready with the second insightful, succinct, satisfying and readable form of some of Prof. William Sweet’s recent reflections on religion.